Analysis of installing ballast water treatment equipment on bulk carriers - Šateikienė, Diana; Janutėnienė, Jolanta; Čerka, Jonas (Transport, 2018)
In order to protect the world from the invasive species of organisms the cleaning ballast water is required, in other words, discharged water must meet requirements posted by the International Maritime Organization (IMO). The paper provides a comparative analysis of ballast water treatment equipment and its technical parameters. The research has been performed to analyse and assess the effect of the introduced equipment on ship stability, including the effect of its weight, dimensions, performance, price and the efficacy of choice. First published online 29 March 2016